Desain Prototype Sistem Informasi Sekolah Berbasis Web Mobile Di SMK IT Shodiqussalam - Richard Renaldi, Muhammad; Sundari, Las (YHMM PUBLISHING, 2024)
This study aims to design a prototype of a school information system based on mobile web technology as a solution to the need for fast, efficient, and flexible access to information at SMK IT Shodiqussalam. The research methods used include observation, interviews, and system design using a user-centered design approach. The system is designed to support the delivery of academic information, management of student and teacher data, grade and attendance tracking, as well as communication between the school, students, and parents. The design process utilized tools such as Figma for user interface design and UML for system modeling. The resulting prototype was tested through usability testing, which showed that most users found the interface easy to use and the features relevant to their needs. The system is considered feasible for further development as it enhances information transparency, administrative efficiency, and interaction among school stakeholders. Utilizing responsive web technology, the system can be accessed on various devices without the need for additional installations.